EFFECTS OF RADIATION EXPOSURE ON THE HUMAN MICROBIOTA: UNDERLYING BIOLOGICAL MECHANISMS AND HEALTH CONSEQUENCES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Radiation is a physical factor that, under certain conditions, can cause significant biological damage at the cellular and molecular levels. While low-level background radiation is a constant part of our environment and generally poses minimal risk, exposure to elevated levels—whether occupational, accidental, or therapeutic—can disrupt physiological systems and impair host–microbiome interactions. Recent studies have highlighted that radiation not only affects human cells directly, but also influences the composition, diversity, and functionality of the human microbiome, particularly in the gut. The microbiome plays an essential role in regulating immune responses, metabolic pathways, and maintaining epithelial barrier integrity. Ionizing radiation, through the generation of reactive oxygen species, DNA damage, and altered immune signaling, can lead to microbiota dysbiosis, reduced microbial diversity, and increased susceptibility to infection and inflammation. Moreover, changes in microbial populations under radiation stress may affect host resilience, recovery, and long-term health outcomes, including increased risk for malignancies and immune dysfunction. This paper explores the mechanisms by which ionizing and non-ionizing radiation affect microbial ecosystems within the human body and underscores the importance of preserving microbial balance in radiobiological research and medical applications. Understanding these interactions opens the door for microbiome-targeted interventions and bioprotective strategies in radioprotection.